2022
DOI: 10.3389/fpsyg.2022.800683
|View full text |Cite
|
Sign up to set email alerts
|

Animal Crossing and COVID-19: A Qualitative Study Examining How Video Games Satisfy Basic Psychological Needs During the Pandemic

Abstract: The COVID-19 pandemic has affected the way many people live their lives. The increasing amount of time spent indoors and isolated during periods of lockdown has been accompanied by an increase in the time people spend playing video games. One such game which soared in popularity during the early stages of the pandemic was Animal Crossing: New Horizons. Through semi-structured interviews with players from different parts of the world, and using a theory-informed qualitative analysis, we document and examine pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…FG and NFG participants also believed video games could meet relatedness needs when they provided a means for friends and family to bond or when in-game relationships transitioned into the real world. Findings from this study resemble results of other qualitative studies showing people are motivated to play video games to experience a sense of control, achievement, and connection (Adachi & Willoughby, 2017 ; Oliver et al, 2016 ; Oswald et al, 2014 ; Przybylski et al, 2010 ; Yee & Sng, 2022 ). However, the qualitative literature on SDT and video games has tended to focus on healthy gaming.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…FG and NFG participants also believed video games could meet relatedness needs when they provided a means for friends and family to bond or when in-game relationships transitioned into the real world. Findings from this study resemble results of other qualitative studies showing people are motivated to play video games to experience a sense of control, achievement, and connection (Adachi & Willoughby, 2017 ; Oliver et al, 2016 ; Oswald et al, 2014 ; Przybylski et al, 2010 ; Yee & Sng, 2022 ). However, the qualitative literature on SDT and video games has tended to focus on healthy gaming.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, Przybylski et al ( 2010 ), across a series of studies, found the more video games satisfied autonomy, competence, and relatedness needs, the more people tended to play them. Yee and Sng ( 2022 ) interviewed players of the popular social simulation video game Animal Crossing: New Horizons , who described how the game enabled them to create and control their environment (autonomy), achieve meaningful goals (competence), and connect with other players (relatedness). Participants in the Yee and Sng ( 2022 ) study also discussed how meeting these needs through video games supported their psychological well-being amidst the first wave of the COVID-19 pandemic.…”
Section: Basic Psychological Needs and Their Relation To Healthy And ...mentioning
confidence: 99%
“…Gaming has also played a significant role in entertaining children during isolation, even bringing in some cases positive, and non-negative, effects such as improving mental health and helping combat isolation ( Barr and Copeland-Stewart, 2022 ). In fact, video games are functional stress-relieving tools for both children and adults: they are believed to reduce both anxiety and depression and increase other abilities ( Bowman et al., 2022 ; Limone, 2021 ; Yee and Sng, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With close to 2.9 million different applications available on the Google Play Store (Statista, 2021a), we believe that future research using the screenomics approach can engender novel theoretical conceptualizations of smartphone use. For example, previous research have suggested how exposure to certain types of social media posts (Kreling et al, 2022;Meier et al, 2020), playing and participating in video games and its culture (Oliver et al, 2016;Przybylski et al, 2012;Yee & Sng, 2022), and even viewing meaningful memes (Rieger & Klimmt, 2019) can be beneficial for well-being. Such potential meaningful experiences with media (e.g., Oliver, 2022)even during passive social media usecan potentially be understood better with screenomes.…”
Section: Discussionmentioning
confidence: 99%